Information in the Knowledge Management System - V. N. Komaritsa (Informaciâ i Innovacii, 2019)
The definition of «information» is one of the most controversial in science. The paper discusses various definitions and terms used in information theory. Based on the analysis of terminological material, a mental model was prepared showing the place and value of information in the knowledge management system.